Hospital environment hygiene nurse: a key player to reduce healthcare associated infections by multi-resistant organisms. Issue 1 (March 2020) - Paz, V.; Paniagua, M.; Santillán, A.; Alaniz, M.; D'Agostino, L.; Orellana, R.; Rodríguez, C.
Summary: Background: Multi-Resistant Organisms (MRO) healthcare-associated infections (HAI) are closely associated with contamination of surfaces. Outsourced companies are usually in charge of both hospital hygiene and environmental hygiene personnel (EHP) supervision, which can result in bias. Methods: A quasi-experimental study. The intervention was to add the "Hospital Environment Hygiene Nurse" (HEHN). MRO acquired infection rate and MRO acquired colonized rate were calculated, pre and post intervention. Confounding variables: MRO carriage rate upon admission and hospitalisation days median (HDM) were calculated. Results: Median length of stay: 5 days (p=0.85, interquartile range=6 days). Carriage rate upon admission: 4.3% for pre-intervention vs 5.3% post-intervention, dif. (CI 95%): 1% (-1% to 2.9%) p=0.33. MRO acquired infection rate: 4.3% for pre-intervention vs. 2% post-intervention, Standardized Infection Ratio (SIR) (CI 95%): 0.47 (0.25 to 0.87). MRO acquired colonization rate:10.4% for pre-intervention vs. 7.9% post-intervention, SIR (CI 95%): 0.75 (0.53 to 1.07). Conclusions: As a reinforcement to standard infection control (IC) measures in place, the incorporation of an exclusive, full-time HEHN was significantly useful to reduce MRO HAI.